Common Comorbidities Among Stroke Patient and Their Outcome in a Tertiary Care Hospital, Bangladesh (Bangladesh Journal of Medicine, 2021)
Background: Stroke is worldwide second leading cause of death and the most common cause of disability. The aim of the study is to evaluate the common comorbidities and their impact on hospital outcome in patients after strokeMethods: This observational study was carried out amongst 228 of acute stroke patients after fulfills the inclusion and exclusion criteria and were admitted indifferent medicine unit of Bangabandhu Sheikh Mujib Medical College Hospital, Faridpur, Bangladesh from May 2020 to April 2021. All cases were confirmed by CT scan or MRI of brain. Stroke were categorizes as Ischemic stroke, Intra-cerebral hemorrhage (ICH) and Subarachnoid hemorrhage (SAH). HTN, DM, IHD were considered as common comorbidities. Prognostic factors were included stage II or III hypertension, altered level of consciousness, previous stroke and large size of stroke.Results: In this study, male affected more than female (68.42% vs 31.58% and ratio 2.1:1). Age >60 years were more affected (68.86%). Most affected patients were Ischemic stroke (61.40%), then ICH (34.21%) and then SAH (3.07%). Common comorbidities were HTN and DM (48.68% and 34.64% respectively). Most of expired patients had comorbidities (80.64%). Worst prognostic factors were altered level of consciousness, stage II or III hypertension and large size of stroke (27.19%, 25.0% and 19.29% respectively). Among hospital outcome most of patients improved and discharged eventfully (41.22%), Deteriorate (17.98%), remain static and discharged (14.03%) and death 13.59%.Conclusion: The most of patients had been suffered from ischemic stroke which were more common in male. The commonest risk factor of stroke was hypertension followed by diabetes mellitus and ischemic heart disease. Our pooled result showed that majority of the patients were improved and discharged and around one sixth of stroke patients have died during hospitalization. The control of comorbid conditions will be much help for prevention of occurrence of stroke and will reduces the disability from stroke events.Bangladesh J Medicine July 2022; 33(1) : 8-11